2012
DOI: 10.1128/jcm.05315-11
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Mycobacterium leprae Strains among Cases in a Rural and Urban Population of Maharashtra, India

Abstract: bThe elimination of leprosy continues to be a challenge, with the disease remaining endemic in several countries. India accounts for the highest number of cases, and the identification of child cases indicates recent transmission. Genetic markers, like variable-number tandem repeats (VNTRs) and single-nucleotide polymorphisms (SNPs), have been identified to track transmission of the pathogen Mycobacterium leprae. They were used to describe M. leprae strains detected in 48 skin biopsy specimens from leprosy pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
(24 reference statements)
1
10
0
Order By: Relevance
“…On the whole, our study showed a distribution of M. leprae with the 1D SNP subtype being dominant, followed by 1C, 1A and 2G from India, which is similar to that reported from Nepal and Bangladesh [19]. One of the previous studies from Western India in a rural and urban area near Mumbai reported mainly subtype D, followed by B [29].…”
Section: Discussionsupporting
confidence: 88%
“…On the whole, our study showed a distribution of M. leprae with the 1D SNP subtype being dominant, followed by 1C, 1A and 2G from India, which is similar to that reported from Nepal and Bangladesh [19]. One of the previous studies from Western India in a rural and urban area near Mumbai reported mainly subtype D, followed by B [29].…”
Section: Discussionsupporting
confidence: 88%
“…In 2009 itself, Cebu, Philippines leprosy patients have strain typed and predominant copy number 8,9,5,15,3,9,14,9,5,7,21,24, . Like South India leprosy patients, North India and Mumbai leprosy patients were also strain typed and these results were somewhat resembles with the South Indian leprosy patients [37,38].…”
Section: Reviewmentioning
confidence: 58%
“…Analysis of allele frequencies of these VNTRs from published data from North India (Lavania et al, 2011), South India (Shinde et al, 2009) and Maharashtra (Kuruwa et al, 2012), suggested a number of demographic associations among strains of M. leprae. Strains from Maharashtra and South India have an identical predominant allele except (AC)8a and 6-7 with the 8 and 6 allele being predominant respectively in our strains.…”
Section: Discussionmentioning
confidence: 96%
“…Each sample is represented as having a distinct profile which may be attributed to polymorphic VNTR loci. Fontes et al, 2009Fontes et al, , 2012Sakamuri et al, 2009;Shinde et al, 2009, Kuruwa et al, 2012. Our study has been carried out with the aim of analysing various known genomic markers to elicit epidemiologically relevant information about the transmission of the disease and to compare strain types within the studied population with VNTRs.…”
Section: Discussionmentioning
confidence: 98%